Histopathologic Finding of Both Gastric and Respiratory Epithelia in a Lingual Foregut Cyst - Yangfan Luo; Nick Shillingford; Jeffrey A. Koempel (Case Reports in Medicine)
Foregut cysts are uncommon, mucosa-lined congenital lesions that may occur anywhere along the gastrointestinal or respiratory tract and typically present within the first year of life. Although infrequent, these cysts may generate feeding or respiratory difficulties depending on the size and location of the lesion. Foregut cysts of the oral cavity are rarely seen and of those cases localized to the tongue are even more uncommon. We describe a 4-month-old girl with a foregut cyst involving the floor of mouth and anterior tongue. Subsequent histologic analysis demonstrated a cyst lined with both gastric and respiratory epithelia. This case represents an extremely rare finding of both gastric and respiratory epithelia lined within a single cystic structure in the tongue. Although a very rare finding, a foregut cyst should be on the differential diagnosis of any lesion involving the floor of mouth or tongue in an infant or child.